Importance of copyrights in online society - Czetwertyński, Sławomir (Managerial Economics, 2018)
The subject matter of the considerations in this paper is copyrights and their importance in the online society. This issue was selected because of the weight of the copyrights in the access and exchange of content via the Internet and, at the same time, the relatively high rate of unauthorized copying that, in fact, translates as a breach of the copyrights. In practice, this means that copyrights (which, for the online society, are what ownership rights for the industrial society are) have no serious authority. Informal norms of the exchange of digital information goods (called the “copy culture”) are not accordant with regulations of the formal copyright institution. The main goal of this paper is to determine the importance of copyrights for relationshipstaking place in the online society. In the paper, a large part of the considerations regards the bi-polarity of the copyright idea that protects authors on the one hand yet prevents the s called author's monopoly on the other. In the course of considerations, the author made an attempt to verify the hypothesis stating that the bi-polarity of copyrights responds to the needs of the online society; however, the formal copyright institution has no such serious authorityas the institution of ownership rights to tangible things. The research method applied in this paper is of a deductive nature. Considerations are based on an analysis of the copyright idea as well as on the traffic, extent, and content on the Internet – in other words, flows within the online society.